2006
DOI: 10.1111/j.1742-4658.2006.05474.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR structure of a human FGF‐1 monomer, activated by a hexasaccharide heparin‐analogue

Abstract: The 3D structure of a complex formed by the acidic fibroblast growth factor (FGF‐1) and a specifically designed synthetic heparin hexasaccharide has been determined by NMR spectroscopy. This hexasaccharide can substitute natural heparins in FGF‐1 mitogenesis assays, in spite of not inducing any apparent dimerization of the growth factor. The use of this well defined synthetic heparin analogue has allowed us to perform a detailed NMR structural analysis of the heparin–FGF interaction, overcoming the limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 51 publications
6
66
0
Order By: Relevance
“…The use of oligosaccharides has already been validated as a good model to replace longer HS chains (44). Indeed, many structural and biological studies using oligosaccharides were consistent with the in vivo biological data (36,45). The minimal binding unit for CypB has previously been shown to be an octasaccharide (dp8).…”
Section: Discussionmentioning
confidence: 79%
“…The use of oligosaccharides has already been validated as a good model to replace longer HS chains (44). Indeed, many structural and biological studies using oligosaccharides were consistent with the in vivo biological data (36,45). The minimal binding unit for CypB has previously been shown to be an octasaccharide (dp8).…”
Section: Discussionmentioning
confidence: 79%
“…As the lower panel shows, there was a significant line broadening of most of the FGF-1 signals upon the addition of exdFGFR2IIIc, which causes many of them to remain hidden below the spectral noise. The framed crosspeaks corresponded to groups belonging to highly flexible regions of the protein, whose transverse relaxation time remained largely independent of the overall size of the polypeptide (35). Because the position and intensity of these crosspeaks remained practically the same in the upper and lower panels of the figure, the overall decrease in intensity of the rest of the signals cannot be attributed to 15 N-labeled FGF-1 coming out of solution upon the addition of exdFGFR2IIIc.…”
Section: 5dhps Competes With Heparin For Binding To Fgfrs-mentioning
confidence: 94%
“…The protocol to uniformly labeled 15 N synthesis has already been described (35). C-LYT/aFGF was produced and purified by heparinSepharose chromatography as described previously (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that the conformational equilibrium remains even when the hexasaccharide 2 is within the complex with FGF-1 as a result of interactions with flexible side chains via electrostatic charges. 52,53 The solution structure of the heparin was described by Mulloy et al as an extended helix with four residues per turn 20 that leads to clustering three consecutive sulphate groups directed towards the same side, relative to the central chain, while the subsequent cluster is directed towards the opposite side. The distribution of sulphate group charges in 1 can be considered to be analogous to that of compound 2 but in the reversed directionality (from the reducing to the non-reducing end; see Fig.…”
Section: Discussionmentioning
confidence: 99%